2006
DOI: 10.1084/jem.20052364
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid dendritic cells of melanoma patients present exogenous proteins to CD4+ T cells after FcγRII-mediated uptake

Abstract: Plasmacytoid dendritic cells (pDCs) contribute to innate antiviral immune responses by producing type I interferons. Although human pDCs can induce T cell responses upon viral infection, it remains unclear if pDCs can present exogenous antigens. Here, we show that human pDCs exploit FcγRII (CD32) to internalize antigen–antibody complexes, resulting in the presentation of exogenous antigen to T cells. pDCs isolated from melanoma patients vaccinated with autologous monocyte-derived peptide- and keyhold limpet he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 29 publications
(36 reference statements)
2
73
1
Order By: Relevance
“…We could not find any signs of altered ICOS signaling in the T cells after pDC depletion and we conclude that ICOS ligand-ICOS interactions between pDC and Th cells are unlikely to cause the observed phenotype. (iv) It is believed that pDC has limited capacity to present exogenous Ag via MHC class II [11], although pDC can internalize exogenous Ag-Ab complexes via CD32 and subsequently present Ag on MHC class II [33]. However, at this stage we can neither confirm nor exclude a role for pDC in Ag-presentation in EAE.…”
Section: Discussioncontrasting
confidence: 40%
“…We could not find any signs of altered ICOS signaling in the T cells after pDC depletion and we conclude that ICOS ligand-ICOS interactions between pDC and Th cells are unlikely to cause the observed phenotype. (iv) It is believed that pDC has limited capacity to present exogenous Ag via MHC class II [11], although pDC can internalize exogenous Ag-Ab complexes via CD32 and subsequently present Ag on MHC class II [33]. However, at this stage we can neither confirm nor exclude a role for pDC in Ag-presentation in EAE.…”
Section: Discussioncontrasting
confidence: 40%
“…Previously we have demonstrated that DCIR and FcgRII-mediated uptake of KLH protein induces efficient Ag presentation by human pDCs (15,30). In this study, we showed that human pDCs are capable of processing phagocytosed particulate Ag, and in addition can be activated by particulate TLR-Ls.…”
Section: Uptake Of Particulate Ag and Tlr-ls By Human Pdcs Induces T mentioning
confidence: 59%
“…Activated pDCs have been demonstrated to promote Th1 (31,47) as well as Th2 responses (32,33), underlining their remarkable functional plasticity. The pDCs were shown to prime specific CD4 + and CD8 + lymphocytes against endogenous and exogenous Ags (15,48), viruses (49) and tumor Ags (45). By contrast, when activated by CpG-B pDCs demonstrate a strong immune suppression and induce the differentiation of allogeneic CD4 + CD25 2 T cells into CD4 + CD25 + regulatory T cells (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may therefore be specialized to present Ags, which are available for MHC II loading for longer time periods (such as in viral infection), whereas they are rather poor at presenting soluble Ags (20,21). However, presentation of exogenous Ags to CD4 + T cells in vitro can be achieved by Ag delivery to human PDCs via FcgRIIA (22) or DCIR, for example (23). PDCs have also been demonstrated to cross-present viral Ags derived from infected cells or directly from viral particles to CD8 + T cells in vitro (24)(25)(26), although it is still controversial if this also occurs in vivo (20).…”
mentioning
confidence: 99%